BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Advances in Research on Plant Pathogenic Bacteria. Editors, S. S. Gnanamanickam and A. Mahadevan, Today & Tomorrow’s Printers and Publishers, 24-B/5, Deshbandhu Gupta Road, Karol Bagh, New Delhi-110 005, India, 1988,245 pp., Rs. 395.00 or 65_00. The science of bacteriology including phytobacteriology has made a tremendous progress during the recent years, and has contributed vastly to the understanding of fundamental biology. In India, however, the research emphasis is still on classical aspects of plant bacteriology. Researches on quantitative bacteriology, forecasting, advanced serology, ultrastructure, HR/SR factors, elicitors, durable resistance, biological control,Â plasmid biology, genetics of bacteria, etc. have not yet gathered momentum. The present volume is based on the proceedings of the National Symposium on Phytobacteriology held at the University of Madras, India on March 14-15, 1986, with the main objective to bring the plant bacteriologists together for exchange of views and draftÂ future research strategies. Â Annotated Bibliography on the Diseases and Insect Pests of Potato in IndiaÂ (1933-1988). Editors, Indu Jalali, R. K. Kashyap and S. Singh, published by InternationalÂ Potato Centre, Lima (Peru), Region VI, New Delhi vi+283 pp, 24 cm, paper cover. This compilation is the first of its kind on potato literature in India. It accumulates 56Â years’ research literature generated by the Indian scientists published both in Indian andÂ foreign journals and contains a total of 954 references. The compilation is based uponÂ both primary and secondary abstracting journals. One hundred journals and eight monographs was scanned for collecting the information. The ’World list of ScientificÂ Periodicals’ was used for journals’ abbreviations. The indexes provided are very useful.Â However, instead of the subject index, the "Word in title index" has been provided. Â